2007
DOI: 10.1016/j.neurobiolaging.2006.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of cerebral ventricular expansion in the Cardiovascular Health Study

Abstract: Interactions between prevalent late-life medical conditions and expansion of the cerebral ventricles are not well understood. Thirty elderly subjects received three magnetic resonance (MR) scans each, in 1997-1999, 2002-2004, and 2003-2005. A linear expansion model of MR-measured lateral ventricle volume was estimated for each subject by fitting a line to a plot of their 1997-1999 and 2002-2004 by the linear expansion model. Ventricular acceleration was analyzed in a multivariate model with age, race, hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 36 publications
4
19
1
Order By: Relevance
“…In agreement with prior reports14, 43, we found a significant effect of age on the shape and size of the lateral ventricles. This effect is most pronounced in the frontal horns perhaps as the result of structural changes in one or more tissue classes in the frontal lobes44–47.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with prior reports14, 43, we found a significant effect of age on the shape and size of the lateral ventricles. This effect is most pronounced in the frontal horns perhaps as the result of structural changes in one or more tissue classes in the frontal lobes44–47.…”
Section: Discussionsupporting
confidence: 93%
“…The bottom rows show the significance of these reductions, revealing highly significant atrophy in AD but a more anatomically restricted atrophic pattern in MCI. In MCI (b), atrophy is most prominent in the left hippocampus; as expected (Carmichael et al, 2007a, b), ventricular expansion is also substantial. When MCI is compared with AD (c), additional temporal lobe degeneration is evident.…”
Section: Figuresupporting
confidence: 64%
“…Ventral striatum and hippocampal volumes are associated with incident AD over a 4.5-year follow-up period [43], and hippocampal volume and MRI-infarcts are independent predictors of incident dementia [67]. Ventricular expansion is faster in subjects who develop MCI [70], and these rates can be increased by diabetes mellitus and hypertension [71]. Our data are important in this context because we found that hypertension and the presence of markers of cerebrovascular disease were significant predictors of the volumes of the mesial temporal lobe and the precuneus.…”
Section: Discussionmentioning
confidence: 99%